Blockade of colon cancer metastasis via single and double silencing of PCSK7/PCSK9: enhanced T cells cytotoxicity in mouse and human - Delia Susan-Resiga; Nabil G Seidah; Nathalie Labrecque; Jean-Sebastien Delisle; Leila Jafarzadeh; Chloé Porcheron; Mailys Le Devehat; Anna Roubtsova; Hadi Bayat; Alexandra Evagelidis; Vatsal Sachan; Alexie Fonta Holder; et al. (Journal for ImmunoTherapy of Cancer)
Background Immunotherapy approaches based on T cells provided breakthroughs in cancer treatment but could cause many immune-related adverse events, and their efficacy is limited for many cancers with an acquired dysfunction/exhaustion of T cells. The present study presents a novel role in immunity for proprotein convertase subtilisin-kexin 7 (PCSK7), the seventh proprotein convertase of the 9-membered secretory proprotein convertase subtilisin-kexin (PCSK)-family.Methods We analyzed cell surface levels of various immune checkpoint proteins in human and mouse cell models in the presence or absence of PCSK7 expression. Injection of mouse colon carcinoma MC38 cells in the spleen of mice lacking either Pcsk7, Pcsk9 or both (double knockout) allowed the analysis of the extent of hepatic tumor metastasis. We also estimated the cell surface expression of checkpoint proteins in CD4+ and CD8+ T cells from healthy human subjects in which PCSK7 expression was silenced by CRISPR Cas9 gRNA knockdown.Results Bioinformatic and cellular studies showed enrichment of PCSK7 mRNA levels in CD8+ T cells, which correlates with those of immune checkpoint proteins (ICPs; eg, LAG3, CTLA4, PD1 and TIGIT) responsible for T-cell dysfunction. Indeed, cells lacking PCSK7 and CD8+ T cells derived from Pcsk7−/− mice exhibited ≥40% lower cell-surface levels of ICPs. Similarly, CRISPR-Cas9 editing of PCSK7 (PCSK7i) in primary human T cells resulted in lower expression of ICPs and a reduced proportion of cells expressing multiple ICPs, without altering the expression of activation markers. Moreover, proprotein convertase subtilisin-kexin 9 (PCSK9), the ninth PCSK family member, enhances the degradation of the low-density lipoprotein-receptor and major histocompatibility complex-I proteins. Indeed, Pcsk9−/− mice were previously reported to exhibit reduced liver tumor metastasis. In the present studies, we report synergistic and complementary functions of PCSK7 and PCSK9, as the loss of each one of the convertases reduced by twofold the number of liver metastases, but the strongest reduction (>90%) was observed in double KO (Pcsk7−/−, Pcsk9−/−) mice. In Pcsk7−/− mouse tumors the antitumorigenic activity of CD8+ T cells was enhanced and the levels of ICPs were reduced.Conclusions Cumulatively, our data provide a PCSK7i strategy to reduce the levels of cell-surface ICPs, thereby rationalizing the use of PCSK7i in T-cell immunotherapies alone or in combination with a PCSK9 inhibitor/silencer.